Short-Cycle Therapy with Bictegravir/Emtricitabine/Tenofovir Alafenamide in a Small Cohort of Virally Suppressed People Living with HIV: A Long-Term Follow-Up - Massimiliano Lanzafame; Emanuela Lattuada; Andrea Delama; Giovanni Mori; Sandro Vento (Biomedicines)
Background: Antiretroviral triple therapy has considerably reduced morbidity and mortality in people living with HIV and is the standard-of-care treatment. However, it is lifelong and linked to long-term side effects and adherence problems. Methods: Here, we report long-term virological and immunological outcome in 12 virally suppressed people on short-cycle therapy with bictegravir/emtricitabine/tenofovir alafenamide administered five days a week (Monday to Friday). Results: All patients, after a long term follow-up, were virally suppressed Conclusions: In the wait for new long-acting antiretroviral drugs and new antiretroviral formulations, short-cycle therapy has proven to be a safe and effective alternative to the standard daily antiretroviral regimen for individuals living with HIV who are virologically suppressed.